Theory of Mind differences in older patients with early‐onset and late‐onset paranoid schizophrenia. (14th January 2013) - Smeets‐Janssen, M. M. J.; Meesters, P. D.; Comijs, H. C.; Eikelenboom, P.; Smit, J. H.; de, L.; Beekman, A. T. F.; Stek, M. L.
<x xml:space="preserve">Abstract</x> Objective Theory of Mind (ToM) is considered an essential element of social cognition. In younger schizophrenia patients, ToM impairments have extensively been demonstrated. It is not clear whether similar impairments can be found in older schizophrenia patients and if these impairments differ between older patients with early‐onset and late‐onset schizophrenia. Methods Theory of Mind abilities were assessed using the Hinting Task in 15 older patients (age 60 years and older) with early‐onset paranoid schizophrenia, 15 older patients with late‐onset paranoid schizophrenia and 30 healthy controls. ANCOVA was performed to test differences between groups. Analyses were adjusted for level of education. Effect sizes, partial eta squared (ε2), were computed as an indication of the clinical relevance of the findings. Results Patients with early‐onset schizophrenia scored significantly lower on the Hinting Task (mean 16.1; SD 4.3) compared with patients with late‐onset schizophrenia (mean 18.6; SD 1.5) and with healthy controls (mean 19.0; SD 1.4). The effect size of this difference was large (ε2 = 0.2). Conclusions These results suggest that ToM functioning may be a protective factor modulating the age at onset of psychosis. Further studies into the relationship between social cognition and onset age of psychosis are warranted. Copyright © 2013 John Wiley & Sons, Ltd.